IMPROVING STUDENTS’ READING ACHIEVEMENT BY USING THINK-PAIRSHARE - Lailatus Sa’adah (Edumedia : Jurnal Keguruan dan Ilmu Pendidikan, 2020)
This research aimed to find out how Think-Pair-Share technique can improve students’ achievement in reading comprehension. It used Classroom Action Research (CAR) and conducted two cycles, where each cycle consisted of four meetings. The subjects are 17 students of XI grade which consists of 7 males and 10 females. The instrument for collecting data were reading comprehension test, observation sheets, and interview sheet. Based on reading comprehension score, students’ score kept improving in every test. In preliminary study the mean score was 34.1, in cycle I the mean score was 73.82, in cycle II the mean score was 89.41. Based on observation sheets and interview sheet, it was found that teaching and learning process ran well. Students were active and interested in reading comprehension. The result of the research showed that Think-Pair-Share can improve students’ achievement in reading comprehension.